Effect of widowhood on the risk of disability among the elderly in China - Pang, Jiahui; Xu, Shouyi; Wu, Yuanyang (Frontiers in Psychiatry, 2023)
Background The deteriorating health status of widowed elderly individuals becomes an important restriction factor affecting healthy aging in China. This paper aimed to find effective ways to reduce the risk of disability among the widowed elderly. Methods An empirical analysis was conducted by using four surveys from the China Health and Retirement Longitudinal Study (CHARLS) in 2011, 2013, 2015, and 2018. A fixed-effects model was performed to estimate the effect of widowhood on the disability risk of the elderly in China and its disparities in different groups, and influencing channels and moderating effects were further investigated. Results Widowhood significantly increased the risk of disability, and the results were robust. The risk of disability was higher among those who were male, living in urban areas, educated, and 60-to-70-years-old. Possible channels in the association were psychological stress and unhealthy behavior. Meanwhile, more financial support, contact from children, and social activities decreased the risk of disability. Conclusion The health risks of older adults after widowhood can be reduced by concerted efforts from society and government, including promoting the traditional Chinese virtue of filial piety and providing health interventions and social support services.